The incidence of infection, diagnosis and treatment of H. pylori in developing countries on the example of Kenya - Dominik Machaj; Sandra Jastrzębska; Katarzyna Cyboran; Alicja Płaczek; Wiktoria Flaumenhaft (Kazimierz Wielki University, 2020)
Introduction: One of the most common causes of bacterial infections in the world is Helicobacter pylori. It has developed mechanisms that allow it to survive in the acidic pH of the stomach. The bacterium contributes to the incidence of gastric ulcer and duodenal ulcer. Infected is about 50% of the world population, while in Africa the proportion is as high as 80%. Despite this there are still number of African guidelines for infection prevention and eradication of the bacterium. Most infections concerns children, adolescents and the elderly. Data on the diagnosis and treatment of patients in Kenya are inconsistent. [1] Doctors are based on international recommendations. No general insurance and a low level of affluence prevent diagnosis of patients at the level of developed countries. Access to endoscopy, and cultures have only wealthy people in big cities. Purpose: Examine the percentage of Helicobacter pylori infection among the people of Kenya, the analysis of the causes of its high value, comparing the diagnosis and treatment with European standards. Material and methods Analysis of causes of hospitalization in 227 hospital patients in Kenya. The majority of them has made winning the test of H. pylori antigen in stool. Analysis of the results of research carried out in 2010Subdepartment Medical Microbiology, Jomo Kenyatta University of Agriculture and Technology in Nairobi, Kenya, where the diagnostic methods was rapid urease test and histological tests. Conclusions The proportion of patients infected with H. pylori in Chuka is 51.9%. Cause of inflammation of the stomach in almost 1/3 of hospitalized patients may be awareness of hygiene and drinking water unsuitable for consumption. Standards of treatment of patients infected with H. pylori do not differ from European guidelines.